Methodology to eliminate errors in machiningprocesses through Augmented Reality Applications - Meraz Méndez, Manuel; Reynoso Jardón, elva (2021)
Today, precision machining companies must implement new technologies to meet the requirements of theaerospace and automotive industries to maintain their competitiveness in the market and create new businessopportunities. It has currently been observed that machining companies face errors in their processes thataffect the quality of the products, the operation of the process, the useful life of the machines, and the tools.This research project aims to develop a methodology to reduce errors in Computerized Numerical Controlmachining (CNC) processes with Augmented Reality Applications (AR-Apps) that help operators interpretmanufacturing drawings and assembly operations optimize Setup operations and ensure the reliability ofthe machining. It begins with a questionnaire applied to a sample of machining companies from ChihuahuaMexico City. To identify the factors that generate critical errors in the machining processes. The main resultsobtained in this paper are reduction of downtime, elimination of scrap, increment cutting tools life, optimizethe machining process, increase productivity, and improved product quality. AR -apps implementation offersa low-cost alternative solution that operators and technicians can use very easily because it is a powerful toolthat helps work more efficiently through virtual environments, reducing errors and optimizing the process ofmachining.